Prevalence and molecular characteristics of Shewanella infection in diarrhea patients in Beijing, China 2017–2019 - Kang, Ying; Yu, Keyi; Huang, Zhenzhou; Pang, Bo; Liu, Shengtian; Peng, Tao; Li, Ying; Wang, Duochun (Frontiers in Microbiology, 2024)
Shewanella spp. are a group of gram-negative bacteria frequently isolated from clinical samples of patients with diarrhea. However, there are few reports on the distribution and characteristics of Shewanella in the diarrheal pathogen spectrum. In this study, 1104 fecal samples were collected, and the Shewanella detection rate was 2.36% (26/1104).The main manifestations of infection caused by Shewanella spp. were diarrhea (100%, 26/26), abdominal pain (65.38%, 17/26), and vomiting (38.46%, 10/26). Average nucleotide identity analysis classified these 26 isolates into three species: S. algae (n = 18), S. indica (n = 5), and S. chilikensis (n = 3). Multilocus sequence typing further classified the isolates into 24 sequence types. In the phylogenetic analysis, core genome single nucleotide polymorphism-based evolutionary tree identified three clone groups corresponding to three infection events in the same months in 2017 and 2019. The putative virulence-associated gene pool consisted of 56 potential virulence genes, including 19 virulence gene factors. However, the virulence gene profiles of different Shewanella species were not necessarily identical. The resistance rates of the 26 isolates to 17 antibiotics from high to low were as follows: polymyxin E (76.92%), cefotaxime (57.69%), ampicillin (50%), ampicillin-sulbactam (34.62%), nalidixic acid (15.38%), ciprofloxacin (11.54%), selectrin (3.846%,1/26), and tetracycline (3.846%, 1/26). The rate of multidrug resistance was 38.46% (10/26). Our research suggests that monitoring for Shewanella spp. should be added to the routine surveillance of infectious diarrhea during the epidemic season.